2017
DOI: 10.1155/2017/3759153
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Injury and Albuminuria in Experimental Hyperuricemic Model Rats

Abstract: Although hyperuricemia is shown to accelerate chronic kidney disease, the mechanisms remain unclear. Accumulating studies also indicate that uric acid has both pro- and antioxidant properties. We postulated that hyperuricemia impairs the function of glomerular podocytes, resulting in albuminuria. Hyperuricemic model was induced by oral administration of 2% oxonic acid, a uricase inhibitor. Oxonic acid caused a twofold increase in serum uric acid levels at 8 weeks when compared to control animals. Hyperuricemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…This finding is analogous to our recent report by increasing serum UA by administration uricase inhibitor oxonic acid in the rats in which XO activity was downregulated by increase in intracellular UA (Asakawa et al. ). We need to elucidate the molecular mechanism on the linkage between cell UA and NOX4 activation in the future.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is analogous to our recent report by increasing serum UA by administration uricase inhibitor oxonic acid in the rats in which XO activity was downregulated by increase in intracellular UA (Asakawa et al. ). We need to elucidate the molecular mechanism on the linkage between cell UA and NOX4 activation in the future.…”
Section: Discussionsupporting
confidence: 92%
“…The result showed that UA in the medium clearly increased NOX4 expression, suggesting that increased UA within the cell may be causative in increasing NOX4 expression independently of XO activity. This finding is analogous to our recent report by increasing serum UA by administration uricase inhibitor oxonic acid in the rats in which XO activity was downregulated by increase in intracellular UA (Asakawa et al 2017). We need to elucidate the molecular mechanism on the linkage between cell UA and NOX4 activation in the future.…”
Section: Oxidative Stresssupporting
confidence: 87%
See 2 more Smart Citations
“…Electron microscopy of kidney biopsies from patients with gout revealed varying degrees of podocyte proliferation and damage [ 78 ]. Signs of significant albuminuria were found in hyperuricemic model rats, accompanied by upregulation of desmin, a podocyte injury marker, and downregulation of podocin, a key component of the podocyte slit diaphragm [ 79 , 80 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%